Biodiesel production from Calophyllum inophyllum oil using zinc doped calcium oxide (Plaster of Paris) nanocatalyst. (May 2019) - Naveenkumar, R.; Baskar, G.
Graphical abstract: Highlights: The Zn doped CaO nanocatalyst was synthesized from waste Plaster of Paris. The size of nanocatalyst was confirmed by SEM analysis. The highest biodiesel yield of 89% was obtained. The fatty acid methyl ester was confirmed using GC–MS. Abstract: The present study was mainly focused on the production of biodiesel from Calophyllum inophyllum oil. The oil was characterized by GC–MS and stored for biodiesel production. The heterogeneous catalyst was synthesized for effective production of biodiesel. The synthesized catalyst was found to have good activity and stability. The surface and element characterization of zinc doped calcium oxide was characterized by SEM and EDAX. The size of nanocomposite was found to be in the range of 14.3–65.6 nm. The EDAX has confirmed the presence of zinc on the surface of the calcium oxide. The maximum biodiesel yield of 89.0% (v/v) was obtained at 55 °C in 80 min and catalyst concentration of 6% (w/v). The optimized methanol:oil molar ratio was obtained at 9:1 for the production of biodiesel. The produced methyl ester was confirmed by GC–MS analysis.